Adding computed tomography and transcranial Doppler findings to the ABCD2 score to predict long‐term risk of stroke after transient ischaemic attack or minor stroke. (2nd December 2014) - Fu, J.; Tang, J.; Yang, J.; Chen, X.; Chen, Y.; Leung, T. W.; Mok, V.; Soo, Y.; Wong, K. L.
<x xml:space="preserve">Abstract</x> Background and purpose The ABCD2 score can predict the early risk of stroke after transient ischaemic attack or minor stroke. However, there is no simple and practical assessment method for the long‐term risks. Computed tomography (CT) and transcranial Doppler (TCD) findings were added to the ABCD2 score to build an ABCD2L2 score and whether the new scoring system could improve the predictive value of the ABCD2 score for the long‐term risk of stroke was determined. Methods From January 2004 to December 2005, all patients with a definite diagnosis of transient ischaemic attack or minor stroke at the Prince of Wales Hospital were consecutively enrolled and followed up until August 2008. CT and TCD were performed. The areas under the curve were used to quantify the ABCD2 and ABCD2L2 scores and related items. Results All 481 patients completed the follow‐up. The shortest follow‐up time was 0.17 months (until death), the longest follow‐up time was 55.60 months and the mean follow‐up time was 40.3 ± 11.0 months. In total, 277 (57.6%) patients showed lesions on CT scans and 195 (40.6%) patients were found with intracranial large artery atherosclerosis. Further strokes occurred in 74 (15.4%) patients, including four (0.83%) patients who died of ischaemic stroke during the follow‐up period. The area under the curve increased from 0.650 (0.586–0.715) for the ABCD2 score to 0.700 (0.637–0.764) for the ABCD2L2 score. Conclusion Adding CT and TCD results to the ABCD2 score to increase its predictability for long‐term risk of stroke recurrence might be a meaningful exploration.